PEMANFAATAN SERAT TANAMAN TEBU SEBAGAI BAHAN BAKU TEKSTIL - Simson Purnomo, dan Arif Susilo, Hidayatun M., Agung Wahyudiono, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research is intended to know 1) the production process of textile from sugarcane fiber, 2) the difference of tensile strength between the textiles from sugar canefiber and those from cotton fiber.This research employed experiment method, involving sugar cane fiber and cottonfiber textile as independent variable. The dependent variables include the tensile strengthand absorpsion of textile. This research was conducted from Februari to Juni 2007 inEngineering Faculty Laboratory of Yogyakarta State University and handicraft andbatik gallery of Yogyakarta.Key Words: sugar cane fiber textile, cotton fiber textile, textil tensile strength, textileabsorpsion.